2010
DOI: 10.1097/shk.0b013e3181cc0183
|View full text |Cite
|
Sign up to set email alerts
|

Vagus Nerve Stimulation Regulates Hemostasis in Swine

Abstract: The central nervous system regulates peripheral immune responses via the vagus nerve, the primary neural component of the cholinergic anti-inflammatory pathway. Electrical stimulation of the vagus nerve suppresses pro-inflammatory cytokine release in response to endotoxin, I/R injury, and hypovolemic shock and protects against lethal hypotension. To determine the effect of vagus nerve stimulation on coagulation pathways, anesthetized pigs were subjected to partial ear resection before and after electrical vagu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
38
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 25 publications
4
38
0
1
Order By: Relevance
“…Using rotational thromboelastography, we observed that electrical VNS significantly reduces reaction (r) time of systemic blood compared with baseline values [46]. Thrombin generation studies revealed that compared with baseline values, blood from the injury site has significantly higher TAT concentrations in vagus nerve stimulated animals versus sham-stimulated animals [46].…”
Section: Tmmentioning
confidence: 96%
See 2 more Smart Citations
“…Using rotational thromboelastography, we observed that electrical VNS significantly reduces reaction (r) time of systemic blood compared with baseline values [46]. Thrombin generation studies revealed that compared with baseline values, blood from the injury site has significantly higher TAT concentrations in vagus nerve stimulated animals versus sham-stimulated animals [46].…”
Section: Tmmentioning
confidence: 96%
“…To explain these improvements in hemostasis, hemodynamic parameters and measures of circulating cells and clotting function in systemic blood and shed blood from the injury site were analyzed via thromboelastography, platelet aggregometry and ELISA for thrombin-antithrombin (TAT) complexes [46]. Despite an initial concern for vagal parasympathetic effects on the heart, electrical VNS had no appreciable effect on either heart rate or blood pressure.…”
Section: Tmmentioning
confidence: 99%
See 1 more Smart Citation
“…In experimental soft tissue injury, haemorrhage is reduced after vagal nerve stimulation. 41 Diminished efferent (parasympathetic) activity, which contributes to baroreflex dysfunction, is promoted by inflammatory mediators, opiates, and anaesthetic agents. 42 43 Further loss of parasympathetic neural activity triggered by haemorrhage, reperfusion, and consequent inflammation during major surgery may therefore be particularly detrimental.…”
Section: Discussionmentioning
confidence: 99%
“…Although this study was not designed to prove causality of diminished vagus activity in lethal outcomes, the functional importance for intrinsic anti-inflammatory activity mediated by vagus nerve signaling is strongly supported by experimental evidence that vagotomy in animal sepsis models increases mortality and worsens tissue damage secondary to uncontrolled cytokine release (30, 31). Moreover, experimentally activating the cholinergic anti-inflammatory pathway in preclinical studies of sepsis by vagus nerve stimulation or administration of selective or universal α7 nAChR agonists improves survival, reduces proinflammatory cytokine levels (including HMGB1, implicated as a necessary and sufficient mediator of lethal sepsis in rodent models), and prevents the development of disseminated intravascular coagulation (24, 25, 30, 32, 33) (Figure 4). …”
Section: Implications For Treating Diseasementioning
confidence: 99%